The Effect of Adding Brackish Snail (Faunus ater) Flour to the Feed on the Growth of Dumbo Catfish (Clarias gariepinus) - Sah, Risti; Herman, Roffi Grandiosa; Pratama, Rusky Intan; Haetami, Kiki (Universitas Gadjah Mada, 2024)
Decreased water quality can be caused by fish losing their appetite, resulting in a buildup of food waste in the water. One of the additional ingredients that can be used is brackish snail (Faunus ater) flour. This research aims to determine the effect of adding brackish snail (Faunus ater) flour to feed on the growth of African catfish seeds and the appropriate dosage in feed that can increase the growth of African catfish seeds. The method used in this research was experimental with a Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications. The treatments used were (P0) control, (P1) 10% brackish snail (Faunus ater) flour, (P2) 15% brackish snail (Faunus ater) flour, and (P3) 20% brackish snail (Faunus ater) flour. The test fish used were African catfish fry weighing 3-4 g and 5-7 cm long. The container used is waring with a density of 20 fish per pound. The amount of feed given is 5% of the biomass of African catfish seeds. The observation data were analyzed using Analysis of Variance (ANOVA) with the F test at a test interval of 5%, if there were significant differences, continue with Duncan's multiple range test. The results showed that the addition of 10% brackish snail (Faunus ater) flour gave significant results with the highest absolute length growth of 13.3±0.18 cm, the highest absolute weight growth of 36.2±0.18 g, the highest survival of 98.3±2.8%, the lowest feed conversion ratio was 1.1±0.0.